GREEN HUMAN RESOURCE MANAGEMENT PRACTICES: EVIDENCE FROM PRIMARY DATA ANALYSIS - Richard, Agwa Terwase; Umogbai, Monica Esiebugie; Kwahar, Nguwatsen; Hanmaikyur, Tyoapine Joseph (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This study investigates Green Human Resource Management (GHRM) practices within the food and beverages sector in Nigeria, focusing on how these practices contribute to the sustainability of these companies. A census approach was adopted, encompassing the entire population of 325 staff members from the sector. Data was collected using a validated and reliable questionnaire, with a Cronbach Alpha coefficient of 0.798. The analysis, conducted using SPSS Version 25, revealed key insights into GHRM practices. Results indicated that green recruitment is well-integrated into the companies, with 87.1 of respondents confirming the inclusion of green job descriptions, and 81.6 agreeing that employees are recruited based on their environmental awareness. Green training is also emphasized, with 87.1 of respondents agreeing that their companies conduct training on environmental management, and 81.6 confirming job rotation to develop green managers. Green rewards are prevalent, with 85.3 agreeing that employees receive bonuses for environmental achievements. Additionally, 87.1 of respondents agreed that green performance appraisal systems are in place, incorporating green performance indicators. Lastly, 87 of employees felt involved in green initiatives, highlighting active communication and engagement in environmental policies. The findings suggest that GHRM practices significantly enhance the sustainability of food and beverages companies in Nigeria. The widespread adoption of green recruitment, training, rewards, performance appraisal, and employee involvement underscores the importance of aligning HR practices with environmental goals for improved sustainability and business performance.